2014
DOI: 10.1371/journal.pone.0092778
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Birth and Antidepressant Medication Use during Pregnancy: A Systematic Review and Meta-Analysis

Abstract: IntroductionPreterm birth is a major contributor to neonatal morbidity and mortality and its rate has been increasing over the past two decades. Antidepressant medication use during pregnancy has also been rising, with rates up to 7.5% in the US. The objective was to systematically review the literature to determine the strength of the available evidence relating to a possible association between antidepressant use during pregnancy and preterm birth.MethodsWe conducted a computerized search in PUBMED, MEDLINE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
80
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 88 publications
13
80
0
3
Order By: Relevance
“…Clinicians and patients need to balance the potential small increase in the risk of PPHN, along with other risks that have been attributed to SSRI use during pregnancy, 37,38 with the benefits attributable to these drugs in improving maternal health and well-being. 39…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians and patients need to balance the potential small increase in the risk of PPHN, along with other risks that have been attributed to SSRI use during pregnancy, 37,38 with the benefits attributable to these drugs in improving maternal health and well-being. 39…”
Section: Discussionmentioning
confidence: 99%
“…30,[41][42][43][44] Meta-analyses and other reports consistently suggest an increase of approximately 1.5-2 fold in the risk for preterm birth (PTB) in women using SSRIs compared to the controls. 26,46,47,[58][59][60] It has been reported that high doses (e.g., more than 40 mg/day for fluoxetine, citalopram, and paroxetine), 61,62 longer exposure, 42,63 and usage during the 2nd and 3rd trimesters 47 seem to be connected with a greater risk of preterm birth. Clinical studies have shown a lack of clear evidence of a negative influence on neurocognitive development with antidepressant usage.…”
Section: Congenital Malformationsmentioning
confidence: 99%
“…48,49,64 Data are also conflicting regarding the relationship between antenatal antidepressant exposure and other neonatal outcomes such as spontaneous abortion, birth weight, persistent pulmonary hypertension, and autism spectrum disorders. 23,26,35,47,[50][51][52][53][54][55][56][57]60,[65][66][67][68][69] Specific information on the risk of other neonatal outcomes in fetuses exposed to clomipramine is lacking. The limited available data suggest that similar to SSRIs, TCAs may be associated with PTB and PNAS.…”
Section: Congenital Malformationsmentioning
confidence: 99%
“…However, it is diffi cult to tease out the infl uence of depression when factors such as drugs, alcohol, and smoking are frequently associated with depression [ 31 -33 ]. The use of antidepressant medication during pregnancy is now commonplace and has been associated with an increased risk of preterm birth [ 34 ]. The underlying mechanism of how depression results in preterm birth is unclear, but there is growing evidence to suggest that stress and infl ammatory markers (C-reactive protein, IL-6, IL-1β, and TNF-α are elevated in depression, and this may relate to the increased risk of preterm birth [ 35 ].…”
Section: Maternal Risk Factors For Spontaneous Preterm Labor and Pprommentioning
confidence: 99%